Corporate Governance: Responsibility Badan Usaha Milik Desa (BUMDes) Panggung Lestari Kalurahan Panggungharjo, Kabupaten Bantul, Yogyakarta - Fikrin (Journal of Society Bridge, 2024)
This research aims to determine how to apply corporate governance principles regarding the implementation of responsibility in Panggung Lestari Village-Owned Enterprises (BUMDes). Technique for selecting research subjects using purposive technique. The informants in this research were the Director and Secretary of BUMDes Panggung Lestari. The data collection used was observation, interviews and documentation. Data analysis techniques are carried out by reducing data, presenting data and conclusions. The results of this research show that the existence of BUMDes Panggung Lestari can provide economic benefits to support community economic activities as a form of responsibility of BUMDes Stage Lestari towards the community and the surrounding environment to achieve the goals of BUMDes itself. Then, the aspect of BUMDes Panggung Lestari's responsibility regarding social benefits for the community is implemented through providing access to employment opportunities, improving the quality of employee human resources, optimizing waste management in peeling business units and allocating social funds.